Asociación entre el ruido ambiental y el trauma acústico en recién nacidos prematuros. - Honorio Silva, María Alejandra (2020)
Noise induced hearing loss is the decrease in the auditory capacity of one or both ears, consequence of damage in the inner ear sensory structures because of the prolonged or repeated exposure to harmful noise levels. In the neonatal intensive care unit (NICU) the noise environment in higher than the rest, hear they are exposed to stress, that include the noises that reach high intensity up to 120 dB (twice as recommended by AAP). In newborns, excessive stimulation of the ciliar cells of corti organ, caused by loud and continuous noises, may result in the destruction, causing progressive hearing loss. Studies have proven that noise causes apnea, hypoxemia, alternant oxygen saturation and increased oxygen consumption secondary to elevated heart and respiratory rate